Measuring Abdominal Visceral Fat Thickness With Sonography: A Methodologic Approach. (March 2018) - Woldemariam, Mulubrhan M.; Evans, Kevin D.; Butwin, Angela N.; Pargeon, Rachel L.; Volz, Kevin R.; Spees, Colleen
This methodological approach to assessing obesity is based on the prepilot work conducted on a small sample of men and women (25-58 years of age) in a laboratory setting. The use of skinfold calipers, body mass index, and sonographic imaging of adipose and visceral fat were obtained. In this pre-experimental work, the rigorous use of sonographic measures of visceral fat demonstrated better trend results than the other measurement tools. The sonographic methods employed were modeled after the work published by Hamagawa et al. All measurements were taken five times, and only the middle three were retained for mean data points. The data are compared and contrasted with a paucity of international studies using sonography to measure visceral adiposity. It is important to determine whether sonography could serve as a non-ionizing imaging technique for the assessment of body composition and a screening technique for cardiovascular disease prediction.